Pengaruh Pelatihan Kader Posyandu terhadap Tingkat Pengetahuan Gizi dan Keterampilan Mengukur Antropometri - Ruth Surya Wahyu Setyaning (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Posyandu plays a crucial role in monitoring the growth and development of infants and toddlers through monthly anthropometric measurements and nutrition and health counseling. Accurate anthropometric data are essential for developing effective nutrition policies. However, measurement techniques performed by Posyandu cadres are often inaccurate, partly due to limited training support. This study aims to examine the effect of training on the knowledge and skills of posyandu cadres about nutrition and anthropometry. A literature search was conducted using Google Scholar with keywords such as “training”, “posyandu cadres” or “posyandu officers”, “skills”, “knowledge”, “anthropometry”, “infants”, “toddlers”. Literature was selected based on the specific inclusion criteria, which included quantitative experimental studies published between 2020 and 2024 focused on posyandu cadres in Indonesia. Studies were excluded if they were not original research, did not examine changes in the knowledge and skills of Posyandu cadres, or did not utilize appropriate data collection instruments. Four studies demonstrated that training positively impacted cadres’ skills in taking anthropometric measurements. One study showed an improvement in the cadres’ ability to detect stunting, and another found an increase in the cadres’ knowledge scores following training. The findings of this study indicate that training for Posyandu cadres can significantly enhance their knowledge of nutrition and their skills in anthropometric measurement, which may influence future policies and interventions.